Viral kinetics analysis and virological characterization of treatment failures in patients with chronic hepatitis C treated with sofosbuvir and an NS5A inhibitor. Issue 5 (22nd December 2017) - Fourati, S.; Guedj, J.; Chevaliez, S.; Nguyen, T. H. T.; Roudot‐Thoraval, F.; Ruiz, I.; Soulier, A.; Scoazec, G.; Varaut, A.; Poiteau, L.; Francois, M.; Mallat, A.; et al.
Summary: Background: The combination of sofosbuvir (SOF) plus an NS5A inhibitor for 12 weeks is highly efficacious in patients with chronic hepatitis C. As the costs of generic production of sofosbuvir and NS5A inhibitor are rapidly decreasing, the combination of these DAAs will be the standard treatment in most low‐ to middle‐income countries in the future. Aim: To identify key predictors of response that can be used to tailor treatment decisions. Methods: A cohort of 216 consecutive patients infected with HCV genotype 1 (1a: n = 57; 1b: n = 77), 2 (n = 4), 3 (n = 33) or 4 (n = 44) were treated with sofosbuvir (SOF) + daclatasvir (n = 176) or SOF + ledipasvir (n = 40) for 12 weeks. The viral kinetics was analysed using the biphasic model and the cure boundary was used to predict time to clear HCV. Results: The overall SVR rate was high (94.4%; n = 204), regardless of the time to viral suppression or low‐level viraemia at the end of treatment. The model‐based predicted HCV RNA levels at the end of treatment could not differentiate patients who did from those who did not achieve SVR. The presence of NS5A resistance‐associated substitutions [position 28 (OR = 70.3, P <.001) and/or 31 (OR = 61.6, P = .002)] at baseline was predictive of virological failure in cirrhotic patients but was not associated with on‐treatment viral kinetics. Conclusion: This real‐world study confirms the excellent results of clinical trials with therapies based on a combination of SOF plus an NS5A inhibitor. It suggests that a personalized approach including baseline NS5A inhibitor resistance testing may inform treatment decisions in cirrhotic patients. Abstract : Linked Content This article is linked to Ferenci and Fourati and Pawlotsky papers. To view these articles visithttps://doi.org/10.1111/apt.14508 andhttps://doi.org/10.1111/apt.14520 .